2006
DOI: 10.3354/meps311125
|View full text |Cite
|
Sign up to set email alerts
|

Water, not food, contributes the majority of strontium and barium deposited in the otoliths of a marine fish

Abstract: We quantified the relative contributions of water and food to strontium (Sr) and barium (Ba) Ba ratios in otoliths were quantified using laser ablation ICP-MS. The relative contributions of water and food sources to otolith aragonite were assessed using a simple linear isotope mixing model. Water sources contributed 83% of Sr and 98% of Ba in otoliths formed in spiked seawater. Our results indicate that water chemistry is the dominant factor controlling the uptake of Sr and Ba in the otoliths of marine fishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
212
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(223 citation statements)
references
References 25 publications
10
212
0
1
Order By: Relevance
“…Under estuarine conditions, bony fish otolith Sr : Ca generally shows a positive correlation with salinity, whereas Ba : Ca typically shows a negative relationship with salinity (Limburg 1995;Elsdon and Gillanders 2005;Macdonald and Crook 2010). Because a large portion of otolith Sr and Ba is derived from the surrounding water (Walther and Thorrold 2006;Webb et al 2012;Izzo et al 2015), fluctuations in Sr : Ca and Ba : Ca can be used to infer the relative salinity of environments experienced by a fish during its lifetime (e.g. Limburg 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Under estuarine conditions, bony fish otolith Sr : Ca generally shows a positive correlation with salinity, whereas Ba : Ca typically shows a negative relationship with salinity (Limburg 1995;Elsdon and Gillanders 2005;Macdonald and Crook 2010). Because a large portion of otolith Sr and Ba is derived from the surrounding water (Walther and Thorrold 2006;Webb et al 2012;Izzo et al 2015), fluctuations in Sr : Ca and Ba : Ca can be used to infer the relative salinity of environments experienced by a fish during its lifetime (e.g. Limburg 1995).…”
Section: Discussionmentioning
confidence: 99%
“…They are, therefore, natural tags whose structure and chemistry provide a record of the environmental history of individuals throughout their lives (Campana 1999), and can reveal movements of present and ancient fish between different water bodies (e.g. Carpenter et al 2003, Walther & Thorrold 2006, Clarke et al 2009, Tanner et al 2011. Nevertheless, most studies in this field (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations on the importance of food on element incorporation into otoliths were highly ambiguous. Walther and Thorrold (2006) concluded that Sr and Ba contents in marine Wsh otoliths clearly reXect ambient Sr and Ba concentrations, while Kennedy et al (2000) reported 70% of the Sr isotopic signature in freshwater Atlantic salmon (Salmo salar) otoliths to originate from food. SigniWcant dietary eVects on strontium incorporation have been demonstrated for American shad (Alosa sapidissima) (Limburg 1995) and Black bream (Girella elevata) (Gallahar and Kingsford 1996) and for strontium and barium incorporation in blueWsh (Pomatomus saltatrix) (Buckel et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…DiVerent analytical methods are commonly used for microchemical studies of Wsh otoliths: Synchrotron X-ray Xuorescence analysis (Tsukamoto et al 1998), particle induced X-ray emission (PIXE; Elfman et al 1999), electron probe microanalysis (HoV and Fuiman 1995), solution based inductively coupled plasma mass spectrometry (ICP-MS; Buckel et al 2004) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS; Walther and Thorrold 2006). In the present study, LA-ICP-MS was chosen to measure feed-dependency on the incorporation of 16 elements because of its high precision in multi-element analysis and good spatial resolution.…”
Section: Introductionmentioning
confidence: 99%